2002
DOI: 10.1007/s00221-001-0997-1
|View full text |Cite
|
Sign up to set email alerts
|

Non-nociceptive upper limb afferents modulate masseter muscle EMG activity in man

Abstract: Recent electrophysiological data obtained in anaesthetized rats evidenced jaw muscle excitatory responses to the electrical stimulation of type II limb somatosensory afferents. In the present work, we describe an inhibitory reflex evoked in human masseter muscles by stimulation of non-nociceptive fibres travelling in the median and radial nerves (MED and RAD, respectively). Eighteen healthy volunteers participated in the study. Subjects were seated on a comfortable chair, with the complex head-mandible-neck-tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…However, previous studies have shown no differences between the latency and amplitude of masseter vestibular-evoked myogenic potentials recorded for ipsilateral and contralateral stimulations using click and tone burst stimuli. 1,8,10,11,15 The recent studies on masseter vestibular-evoked myogenic potentials recording using electrical stimulation on humans 1 do not match the data obtained from animals. 22–24,26 This could be because of the anatomical differences in vestibulomasseteric reflex pathways between humans and animals.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, previous studies have shown no differences between the latency and amplitude of masseter vestibular-evoked myogenic potentials recorded for ipsilateral and contralateral stimulations using click and tone burst stimuli. 1,8,10,11,15 The recent studies on masseter vestibular-evoked myogenic potentials recording using electrical stimulation on humans 1 do not match the data obtained from animals. 22–24,26 This could be because of the anatomical differences in vestibulomasseteric reflex pathways between humans and animals.…”
Section: Discussionmentioning
confidence: 97%
“…14 In humans, static tilt also exerts a bilateral asymmetrical effect on masseter muscles, and the evidence shows that this effect is macular in origin. 15 The natural function of the vestibulomasseteric reflexes is to respond to sudden head tilt upward or downward. 2 For example, if the head is suddenly dropped, the masseter muscle is inhibited.…”
Section: Introductionmentioning
confidence: 99%